An Economic Strategy for the Second Liberation of Africa - Babu, A.M. (Dar es Salaam Mkuki na Nyonta, 2010)
"The real meaning of the African crisis is the that our countries, collectively and individually, are at the dead-end, thanks entirely to the economic and 'development' policies pursued since independence. The situation is so bad that no 'reforms', whether inspired by the World Bank or IMF, or whether initiated locally, can get us out of the mess. For what is needed is not reform but a different outlook which calls for a decisive change of direction, a change from the primitive colonial structure of the economy to a national economy, above all a change in the structure of production. This entails a change from an outward-motivated to an inward-motivated development strategy, whose guiding principle must be based on the recognition that external causes are only a condition of change, and internal causes the baisi of change." So starts this timely and urgent message that Abdulrahman Mohamed Babu addresses to all progressive and radical Africans, some of who in the present situation of triumph of Western capitalism and "democracy" are at loss as where to turn and how to proceed in their search for Africa's "Second Liberation"
Keywords: Democracy, Politics Economic Strategies